Net Ecosystem Exchange of Carbon Dioxide in Rice-Spring Wheat System of Northwestern Indo-Gangetic Plains - Amit Kumar; Arti Bhatia; Vinay Kumar Sehgal; Ritu Tomer; Niveta Jain; Himanshu Pathak (Land, 2021)
Rice growing under anaerobic conditions followed by spring wheat under an aerobic environment differentially impact the net ecosystem exchange (NEE) of carbon dioxide (CO2) in rice-wheat systems of the north-western Indo-Gangetic Plains (IGP). This is the first estimation of the NEE in a rice-spring wheat sequence via the eddy covariance technique in the north-western Indo-Gangetic Plains, which was partitioned into gross primary productivity (GPP) and ecosystem respiration (RE) and correlated with the environmental variables. Higher CO2 uptake of −10.43 g C m−2 d−1 was observed in wheat during heading as compared to −7.12 g C m−2 d−1 in rice. The net uptake of CO2 was 25% lower in rice. The average daily NEE over the crop season was −3.74 and −5.01 g C m−2 d−1 in rice and wheat, respectively. The RE varied from 0.07–9.00 g C m−2 d−1 in rice and from 0.05–7.09 g C m−2 d−1 in wheat. The RE was positively correlated with soil temperature at 5 cm depth (0.543, p < 0.01) in rice and with air temperature (0.294, p < 0.01) in wheat. The GPP was positively correlated with air temperature (0.129, p < 0.05) and negatively correlated with vapor pressure deficit (VPD) (−0.315, p < 0.01) in rice. In wheat, GPP was positively correlated with air temperature (0.444, p < 0.01) and soil moisture (0.471, p < 0.01). The rate of GPP over the crop duration was nearly the same in both rice and wheat, however, the RE was higher in rice as compared to wheat, thus, the ratio of cumulative RE/GPP was 0.51 in rice and much lower at 0.34 in spring wheat. Rice contributed 46% and 43% to the annual totals of RE and GPP, respectively, while spring wheat contributed 36% and 51%. The NEE of CO2 was higher in spring wheat at −576 g C m−2 d−1 as compared to −368 g C m−2 in rice. Thus, while estimating the carbon sink potential in the intensively cultivated northern IGP, we need to consider that spring wheat may be a moderately stronger sink of CO2 as compared to rice in the rice-wheat system.